2004
DOI: 10.1542/peds.2004-0227
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic or Intermittent Hypoxia on Cognition in Childhood: A Review of the Evidence

Abstract: Adverse impacts of chronic or intermittent hypoxia on development, behavior, and academic achievement have been reported in many well-designed and controlled studies in children with CHD and SDB as well as in a variety of experimental studies in adults. This should be taken into account in any situation that may expose children to hypoxia. Because adverse effects have been noted at even mild levels of oxygen desaturation, future research should include precisely defined data on exposure to all levels of desatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
240
0
11

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 377 publications
(255 citation statements)
references
References 87 publications
4
240
0
11
Order By: Relevance
“…A clear dose-effect gradient was observed, which concurs with the generally accepted hypothesis of a causal relationship between hypoxemia and neurocognitive impairment. 15 In addition to moderate hypoxemia (Յ90% SAT min ), mild hypoxemia (91%-93% SAT min ) was significantly associated with impaired performance. This is surprising given that this level of arterial oxygen saturation is frequent in children.…”
mentioning
confidence: 90%
“…A clear dose-effect gradient was observed, which concurs with the generally accepted hypothesis of a causal relationship between hypoxemia and neurocognitive impairment. 15 In addition to moderate hypoxemia (Յ90% SAT min ), mild hypoxemia (91%-93% SAT min ) was significantly associated with impaired performance. This is surprising given that this level of arterial oxygen saturation is frequent in children.…”
mentioning
confidence: 90%
“…18 Another recent study demonstrated that infants have reduced cerebral tissue oxygenation when in the prone position and hypothesized that this reduction in oxygenation may help explain the elevated risk of SIDS while the infant is in this position. 19 Tissue hypoxia clearly leads to increased risk of morbidity in neonates, which demonstrates the importance of identifying infants at risk for hypoxia before discharge to intervene early.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary hypertension is a well-recognised consequence of hypoxia, and the some of the cellular mechanisms are now being elucidated [10]. Chronic hypoxia (even mild levels) has detectable cognitive effects on children [11] and acute hypoxia at altitude affects the mental functioning of adult aircrew [12], even at altitudes <10,000 feet [13]. Thus it is not unreasonable to use hypoxia as a surrogate for clinical risk even though the individual risk of adverse effects from hypoxia remains uncertain.…”
Section: Predicting Risk Of Flight In Individuals: Not a Simple Taskmentioning
confidence: 99%